Substantiation of Organ-Saving Operations in Renal Tumours - K. Sh. Gantsev; Yu. N. Khrizman; A. A. Khmelevskiy; V. K. Shakurov; R. I. Aglyamov (Креативная хирургия и онкология, 2018)
Purpose of the study: to analyse the results of organ-preserving operations in patients with localized renal cell carcinoma.Materials and methods. The results of treatment of 458 patients who underwent organ-preserving treatment for renal cell carcinoma between 2009 and 2017 were analysed and evaluated. Of these, 286 were men (62.4 %) and 172 were women (37.6 %) with an average age of 54.7 ± 2.25 years (between 23 and 84 years).Results. The size of the tumours ranged between two to eight centimetres (average tumour size 4.6 cm). The duration of “open” operations ranged from 30 to 110 minutes (average of 62 minutes); those using laparoscopy lasted between 85 and 180 minutes (average of 146 minutes). The volume of blood loss during the operation was an average of 133.6 ml (from 80 ml to 500 ml). In most patients, the tumour was in the first stage of the disease (443 cases, or 96.7 %). In 17 of patients operated on morphologically, invasion of paranephric fibre at the third stage (3.7 %) was detected. A further 8 patients had a second stage tumour more than 7 cm in size but without germination beyond the kidney (1.7 %). There were no cases of intra- or post-operative mortality. Discussion. No significant differences during the postoperative period were observed in patients undergoing “open” and laparoscopic surgery; the frequency of postoperative complications was also approximately the same in both cases.Conclusion. Improvements in contemporary diagnostic methods have led to a sharp increase in the detection rate of small tumours. The results of studies comparing nephrectomy and kidney resection with a healthy contralateral kidney indicate the validity of the organ-preserving approach with small tumour sizes and localisation convenient for resection. In this regard, recently there has been a trend towards a wider use of kidney resection in renal cell carcinoma. Increased emphasis on the quality of life of cancer patients has led to an active study of the possibilities of using modern technologies in kidney cancer surgery.